Experimental investigation on creep characteristic of the spacer between winding turns of power transformers - Arabul, Ahmet Yigit; Kumru, Celal Fadil; Arabul, Fatma Keskin; Senol, Ibrahim (SAGE PUBLICATIONS LTD, 2021)
The lifetime of insulation in a power transformer deteriorate in time by reason of high electrical/thermal stresses and contaminations from environmental factors. In particular, faults in oil type power transformers due to thermal stress ruin energy continuity and cause serious economic losses. Most of the faults due to thermal stress generally occur at the hot-spot location of transformer windings. Particularly, creeping of the spacer between windings and the resulting thermal stress constitutes a significant part of the transformer failures. Therefore, the determination of creep characteristics under different conditions is important in terms of fault estimation, aging calculations and product development. In this study, it is aimed to acquire creep characteristics and failure time of spacer for different test temperatures. For this reason, a test system is designed to determine the creep characteristics of the spacer between the windings. In order to specify temperature ranges of the tests to be done, thermal analysis is performed for different creep rates of the spacer. The test setup is designed according to the results of thermal analysis, and creep test results are presented. The results indicate that creep characteristics of spacers will provide to make the aging calculations and failure prediction algorithms more accurate.
Keywords: Power transformer; creep characteristic; insulation; spacer; failure; OIL-PAPER INSULATION; KRAFT PAPER; TEMPERATURE; Automation & Control Systems; Instruments & Instrumentation